Illicit business - McCarthy-Jones, Anthea, 1982-; Turner, Mark, 1949- (Routledge, 2025)
Illicit business is big business. It covers a diverse range of activities from money laundering, drug trafficking and human trafficking through to the manufacture of counterfeit goods and the multiple activities in informal and shadow economies. This book introduces the world of illegal business. The authors contextualise the evolution in practices of illegal business around the world, highlighting the importance of organised crime, shadow economies, and informal sectors. Incorporating scholarly insights with real world examples, the book provides a much-needed business and economics analysis of a subject that is otherwise dominated by criminologists. With a range of case studies, this book provides a global approach that will be valuable reading for students seeking to understand the business of crime"- Provided by publisher.